Hydrogen Economy in Ecuador: opportunities and barriers - Posso Rivera, Fausto; Sánchez Quezada, Johanna (ACI Avances en Ciencias e Ingenierías, 2014)
The hydrogen economy, H2, is an emerging energy paradigm proposed to H2 as the vector that drives the development of human society in this century, and as embodied in the energy system Solar Hydrogen SESH where primary sources are renewable, and it is the secondary source H2. A large number of countries are undertaking plans to incorporate the SESH in their energy structure. In this context, this paper argues whose purpose is to identify and analyze the factors involved in the development of SESH in Ecuador, through research supported methodologically on a literature review and a survey of a group of experts involved, from different fields, renewable energy and the H2 as a vector. It is obtained that the country has sufficient potential exploitable renewable energy to ensure the operability of SESH, with hydropower and biomass are the most appropriate sources. Furthermore, the vision of development of the Ecuadorian state, driving the transformation of the energy matrix by the massive incorporation of renewable energy, would favor the gradual penetration SESH, especially in two niche opportunities, rural electrification and urban transport. Barriers are also reported: scarce and scattered research activity; minimum formation of human talent necessary for the operation and innovation in the technologies of H2; absence of a legal and regulatory framework that encourages penetration SESH and the incipient formation of collaborative networks in research and advocacy, in the balance predominate advantages over the barriers. It is concluded that only by agreed action academia, research centers and private companies, under the tutelage of the state will allow this new energy system contributes to sustainable development and conductive Ecuador joining hydrogen economy
Keywords: Energy systems; hydrogen energy; renewable energy; Ecuador